Perancangan Pengendali Kecepatan Motor DC Shunt Menggunakan Metode Sliding Mode Control (SMC) dan Proposional Integral Derivative (PID) - Ahmad Faizal (UIN Sultan Syarif Kasim Riau, 2015)
Shunt DC motor is a DC motor excitation own type of parallel. Shunt field coil windingsare made withlots oftiny wires that have a high resistivity. This is because the shunt DC motor has a simple construction, relatively cheap, and easy maintenance. The down side of shunt DC motor is the motor speed and load torque is relatively difficult to set up. In the event of load changes, the DC shunt motor speed will decrease . To get a constant speed and improve the performance of the motor DC shunt to changes in load , then the need for a shunt DC motor arrangement. In this reseach of the control system on as hunt DC motor speed control. Control technique used is the sliding mode controller and proposinal integral derivative. Based on the observations, the results obtained show that both controllers are sliding mode controller and PID can be used at the plants hunt DC motor speed control. But the results of the comparison speed and control signals simulation show sthat the successive sliding mode controller produces better speed performance than the sliding mode controller with fast transient time in which obtained τ= 0.020s, ts = 0.5%= 0.1, 2%= 0.08, 5%= 0.06s, tr = 0.588s, and td = 0.0138s, overshoot = 0.71%, Error Steady State = 25, and Time Peak (TP) = 375 s.And control signals in successive sliding mode transient time obtained τ = 0.012s, ts = 0.5%= 0.06, 2%= 0.048, 5%= 0.036s, tr =0.0353s, and td = 0.0831s, overshoot = 0.2%, Error Steady State = 5, and Peak Time (TP) = 30 s..Keywords: Control, DC motor shunt , PID, sliding mode